Tariffs and the exchange rate: Evidence from Twitter - Dmitry Matveev; Francisco Javier Ruge-Murcia (Bank of Canada, 2021)
This paper examines the conjecture that an increase in tariffs in a flexible exchange rate regime leads to the appreciation of the local currency. We focus on the reaction of the exchange rate market to tweets by US President Donald Trump regarding possible tariff increases on Canadian and Mexican goods. The anticipation of trade restrictions leads to the US dollar appreciating by 0.023% and 0.051% vis-à-vis the Canadian dollar and Mexican peso within five minutes of the tweet, and comparable percentages for forward rates up to five years ahead. Exchange rate appreciation may mitigate the expenditure-switching intended by the protectionist policy.
Keywords: F13; F31; 330; Exchange rates; Trade integration